Mammalian hybrid prophagophore is a precursor to autophagosomes - Kumar Suresh; Javed Ruheena; Paddar Masroor A; Eskelinen Eeva-Liisa; Timmins Graham S; Deretic Vojo (TAYLOR & FRANCIS INC, 2025)
The precursors to mammalian autophagosomes originate from preexisting membranes contributed by a number of sources, and subsequently enlarge through intermembrane lipid transfer, then close to sequester the cargo, and merge with lysosomes to degrade the cargo. Using cellular and in vitro membrane fusion analyses coupled with proteomic and biochemical studies we show that autophagosomes are formed from a hybrid membrane compartment referred to as a prophagophore or HyPAS (hybrid preautophagosomal structure). HyPAS is initially LC3-negative and subsequently becomes an LC3-positive phagophore. The prophagophore emerges through fusion of RB1CC1/ FIP200-containing vesicles, derived from the cis-Golgi, with endosomally derived ATG16L1 membranes. A specialized Ca2+-responsive apparatus controls prophagophore biogenesis and can be modulated by pharmacological agents such as SIGMAR1 agonists and antagonists including chloroquine. Autophagic prophagophore formation is inhibited during SARS-CoV-2 infection and is recapitulated by expression of SARS-CoV-2 nsp6. These findings show that mammalian autophagosomal prophagophores emerge via the convergence of secretory and endosomal pathways in a process that is targeted by microbial factors including coronaviral membrane proteins.